Religion in the Viking Age Moral Economy : A reading of a lausavísa by Egill Skallagrímsson - Taggart, Declan (Religionsvidenskabeligt tidsskrift, 2022)
ABSTRACT: On those rare occasions when Old Norse religion and morality are set alongside one another, the notion of a non-Christian morality is typically dismissed or Old Norse religion is viewed as actively holding back moral progress. I seek to challenge that rough consensus by examining lausavísa 19 by Egill Skallagrímsson, a short poem that seems to directly link gods with punishing certain forms of conduct. I approach the text with three research questions in mind: 1) Were the gods perceived as being aware of and concerned with human actions? 2) What types of transgressions do they seem to care about? 3) What is their perceived efficacy? Through this process, I seek to improve the modern understanding of the extent to which Old Norse deities were perceived as sympathetic to particular moralities and responsive to abuses against their followers.